The effects of natural organic matter (NOM) fractions on fouling characteristics and flux recovery of ultrafiltration membranes - Zularisam, A. W. (Elsevier B.V., 2007)
Natural organic matter (NOM) which is a complex mix of particulate and soluble materials in surface water has been identified and reported by previous studies as responsible for membrane fouling. However the component of NOM which primarily causes the fouling problem is still not well understood, especially relating to the specific fraction that is mainly responsible for flux decline. Therefore, the main objective of this study is to gain a better understanding on the ultrafiltration membrane fouling characteristics due to fractionated NOMs. The 68 kDa MWCO polysulfone (PSF) and 50 kDa MWCO cellulose acetate (CA) membranes formed by a simple phase inversion technique were employed, and the experiments were carried out in a submerged membrane configuration. The Ulu Pontian River water was fractionated into several components which were hydrophobic (HPO), transphilic (TPI) and hydrophilic (HPI) fractions using DAX-8 and XAD-4 ion exchange resins. The experimental results showed that the HPI component of NOM exhibited the worst flux decline despite lesser DOC and UV254 rejections compared to other fractions (HPO and TPI). On the other hand, the HPO fraction showed the highest DOC and UV254 removals despite possessing lower organics concentration than HPI fraction. Therefore the degree of flux decline is not necessarily proportional with the DOC and UV254 removals and in fact the degree of DOC and UV254 rejections are relatively independent of the amount of organics in the source water. Thus, it is worth to note that rejection and fouling are not greatly dependent on the SUVA and DOC concentrations but mostly on the rejection mechanism resulted from the membrane-feed interactions. The hydraulic resistance in series assessment elucidated that the concentration polarization, adsorptive fouling and cake layer deposition were the dominant fouling mechanisms for HPO, HPI and TPI fractions, respectively. Furthermore the effect of cleaning solutions on flux recovery was found significant in nearly restoring the initial membrane permeability. Surprisingly, the HPI fraction was found to exhibit better flux recovery than HPO fraction despite its higher adsorption resistance (Ra). Therefore, in future applications, the type of fouling resistance and the dominant fouling mechanism are useful tools which can be employed as quantitative measurements for flux recovery and cleaning techniques effectiveness